Characteristic of the study activity in students of Deontology - Hilda Aleida Peguero Morejón (Editorial Ciencias Médicas, 2014)
Introduction: To understand the characteristics of the activity of independent study in the students, it is important inside an academic institution, they constitute an element to know, to understand and to interpret the life in the classroom and each one of the elements that you/they integrate it. Objective: To characterize the behavior of the independent study starting from the indicators as use of the time, organization of the study conditions and concentration and study method in students of the Ability of Odontology "Raúl González Sánchez". Material and method: The investigation is defined as pedagogic with qualitative focus, with the participation of 216 students of an universe of 778, Ability of Odontology "Raúl González Sánchez", I study 2011 - 2012. An autoevaluación survey was applied that consists of 35 closed questions to characterize the independent study in the indicators: I use of the time, organization of the study conditions and concentration and study method that it is used to study. Results: 63,4% of the evaluated students of bad in the use of the time, in the organization of the study conditions and concentration was evaluated of bad 43,5%, while in the study method 15,2% was evaluated of bad. In summary of the 216 students they were evaluated of very well 2,7%, of well 30%, to regulate 42,1% and bad 25%. Conclusions: The use of the time during the independent study constitutes the more affected by the number of evaluated students of bad, continued by that of organization of the study conditions and concentration. Difficulties exist in the organization of the independent study in the students that participated of the study.